Effects of Non-invasive Neuromodulation on Executive and Other Cognitive Functions in Addictive Disorders: A Systematic Review - Schluter, Renée S.; Daams, Joost G.; van Holst, Ruth J.; Goudriaan, Anna E. (Frontiers in Neuroscience, 2018)
Background: In order to improve the current treatment of addictive disorders noninvasive neuromodulation over the dorsolateral prefrontal cortex (DLPFC) has gained attention. The DLPFC is crucially involved in executive functioning, functions which are related to the course of addictive disorders. Noninvasive stimulation of the DLPFC may lead to changes in executive functioning. Currently an overview of effects of neuromodulation on these functions is lacking. Therefore this systematic review addresses the effects of noninvasive neuromodulation on executive functioning in addictive disorders. Methods: The current review is conducted and reported in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses for Protocols 2015 (PRISMA-P 2015) guidelines and has been registered in PROSPERO International Prospective Register of Systematic Reviews (https://www.crd.york.ac.uk/prospero/, registration number: CRD42018084157). Original articles were searched using the Ovid MEDLINE, Embase and PsycINFO database. Results: The systematic search resulted in 1228 unique studies, of which sixteen were included in the current review. Some of these studies do not address the classic definition of executive functions, but another cognitive function. However they were included in this review since the field is small and still under development and we aim to give an inclusive overview in its broadest sense. The following executive and other cognitive functioning domains were assessed: attention, cognitive flexibility, response inhibition, memory and learning, problem solving, social cognition, risk taking, cognitive bias modification and overall executive functioning. The executive function domain most positively affected was social cognition followed by memory & learning, response inhibition, cognitive flexibility and attention. Conclusions: The studies addressed in the current review used a large variability of stimulation protocols and study designs which complicates comparability of the results. Nevertheless the results of these studies are promising in light of improvement of current treatment. Therefore we recommend future studies that compare the effect of different types of stimulation, stimulation sides and number of stimulation sessions in larger clinical trials. This will significantly increase the comparability of the studies and thereby accelerate and clarify the conclusion on whether noninvasive neuromodulation is an effective add-on treatment for substance dependence.